Draft Genome Sequences of Endophytic Pseudomonas spp. Isolated from Grapevine Tissue and Antagonistic to Grapevine Trunk Disease Pathogens - Niem, Jennifer (Microbiol Resour Announc, 2019)
Endophytic strains of Pseudomonas were isolated from grapevine tissues and exhibited antagonistic activity against several grapevine trunk disease pathogens. The draft genome sequences of the four strains revealed the presence of putative gene clusters that may impart biocontrol activity against plant pathogens.